EVALUATION OF MELANIN INHIBITION EFFICIENCY OF C-PHYCOCYANIN EXTRACTED FROM SPIRULINAON ZEBRAFISH (DANIO RERIO) MODEL - Minh-Quan, To; Dinh-Bien, Lai; Thi Mai-Chinh, Tran; Tram-Anh, Le Tran; Quoc-Dang, Quan (Tạp chí Sức khỏe và Lão hóa, 2025)
Melanin overproduction can lead to hyperpigmentation issues such as freckles and melasma, impacting aesthetics and health. This study investigates the inhibitory effects of C-Phycocyanin (C-PC) extracted from Spirulina on melanin synthesis using a zebrafish (Danio rerio) model. C-PC demonstrated significant tyrosinase inhibition and reduced melanin content in zebrafish embryos in a dosedependent manner. The IC50 value of C PC for tyrosinase inhibition was determined to be 38.36 ± 19 µg/mL. At the highest tested concentration (10 µg/mL), C-PC reduced melanin content in zebrafish embryos by approximately 48.57%, compared to 71.08% inhibition observed with kojic acid. Importantly, C-PC exhibited low toxicity, with treated embryos maintaining normal morphology and viability. The findings suggest the potential application of C-PC as a natural depigmenting agent in cosmetic formulations.